More than four decades of medical informatics education for medical students in Germany - Winter, Alfred; Hilgers, R.-D.; Hofestädt, R.; Knaup-Gregori, Petra; Ose, C.; Timmer, A. (Methods of information in medicine, 2013)
The publication of German competency-based learning objectives “Medical Informatics” for undergraduate medical education gives reason to report on more publications of the German journal GMS Medical Informatics, Biometry and Epidemiology (MIBE) in Methods. The publications in focus deal with support of medical education by health and biomedical informatics, hospital information systems and their relation to medical devices, transinstitutional health information systems and the need of national eHealth strategies, epidemiological research on predicting high consumption of resources, and with the interaction of epidemiologists and medical statisticians in examining mortality risks in diabetes, in genome wide association studies and in dealing with limits and thresholds. This report is the beginning of an annual series intending to support better international cooperation to achieve good information as a basis for good medicine and good healthcare.
Publikationsdatum: 22. Januar 2018 (online)
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 16.11.2021